The drama of Luigi Pirandello - Vittorini, Domenico (University of Pennsylvania Press, 2018)
This volume offers a survey and interpretation of all of Pirandello's plays, giving outlines of the plots and criticism, together with a biographical sketch of the Italian dramatist.